Harvesting Systems of Private Forests in Indonesia: A Review - Budiaman, Ahmad; Hardjanto (Jurnal Manajemen Hutan Tropika, 2023)
Private forests are spread over almost all the islands of Indonesia. Private forest harvesting has an important and strategic role in improving the welfare of the Indonesian people, especially in rural areas. Therefore, this research presents a review of harvesting systems used in private forests in Indonesia. This research uses literature searching and a statistical database. The basic criteria for selecting a harvesting system of private forest are a timber sales system, low equipment capital costs, and labor-intensive as well as adaptivity to local wisdom. Harvesting of private forests is mainly carried out by small-scale contractors Forest harvesting systems are partly mechanized and non-mechanized. Chainsaw was the cutting tool used for felling, debranching, and bucking. The most commonly used forest harvesting systems are manual and those involving modified motorbikes. Another less common system is conducted with animals, winches, and simple skyline systems. Loggers in private forests are self-taught workers and have not received special training in harvesting techniques, log bucking and wood extraction, and chainsaw maintenance. Improvement of wood extraction techniques is urgently needed, especially in aspects of the operating system, occupational health, and safety in forest harvesting with modified motorbikes, winches, and simple skyline systems.